Analysis and Synthesis of Cardioid Crank Guide-bar Mechanism with Approximate Dwell Motion - Haotong Han; Zhenzhi He; Jiguang Han (Jixie chuandong)
The cardioid crank is a planet mechanism which is able to generate cardioid curve， with cardioid crank as the driven crank of the guide-bar mechanism is equal to the mechanism which has a crank of the varying length and varying speed and moving along the cardioid， which changed the kinematic characteristics of the guide-bar. A cardioid crank guide bar dwell motion mechanism is presented. The motion analysis and the calculation method of the limit position and oscillate angle of guide-bar are presented. The design method of approximate dwell motion mechanism is studied according to the guide-bar oscillate angle， the minimum length of guide bar is calculated， and the influence of center distance on the motion performance of the mechanism is discussed. The least square method is used to approximate the mechanism parameters.